2019
DOI: 10.7150/thno.29552
|View full text |Cite
|
Sign up to set email alerts
|

Engineering stem cell cardiac patch with microvascular features representative of native myocardium

Abstract: The natural myocardium is a highly aligned tissue with an oriented vasculature. Its characteristic cellular as well as nanoscale extracellular matrix (ECM) organization along with an oriented vascular network ensures appropriate blood supply and functional performance. Although significant efforts have been made to develop anisotropic cardiac structure, currently neither an ideal biomaterial nor an effective vascularization strategy to engineer oriented and high-density capillary-like microvessels has been ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 83 publications
0
43
0
1
Order By: Relevance
“…EC dysfunction within the walls of large arteries is an important contributor to inflammation, barrier dysfunction, blood clotting, hypertension and vascular structural changes 40-45. Various mechanisms induce EC injury and death, which may lead to the detachment of ECs from the vascular wall and thereby cause vascular remodeling 46. Jia et al reported that endothelial dysfunction plays a role in AD development by endoplasmic reticulum stress dependent microparticles derived from smooth muscle cells 47.…”
Section: Discussionmentioning
confidence: 99%
“…EC dysfunction within the walls of large arteries is an important contributor to inflammation, barrier dysfunction, blood clotting, hypertension and vascular structural changes 40-45. Various mechanisms induce EC injury and death, which may lead to the detachment of ECs from the vascular wall and thereby cause vascular remodeling 46. Jia et al reported that endothelial dysfunction plays a role in AD development by endoplasmic reticulum stress dependent microparticles derived from smooth muscle cells 47.…”
Section: Discussionmentioning
confidence: 99%
“…The field of tissue engineering has progressed rapidly, but poor vascularization remains a major obstacle in bioengineering cell-dense tissues, limiting the viable size of constructs due to hypoxia, nutrient insufficiency, and waste accumulation. Prior classical vascularization strategies focused on stimulating vascular ingrowth into tissue constructs, which can be achieved by incorporating growth factors or endothelial cells 26 - 28 . However, these so-called angiogenic approaches are inadequate because the average growth rate of newly developing micro-vessels is only ~5 μm/h 7 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…With the continuous improvement of the production process and formulation, the preparation of the dECM has gradually developed from traditional methods such as lyophilized powder and acid digestion to today's higher fidelity methods such as ultrasonic homogenization, which allows its natural protein structure and function to be better retained [ 100 , 101 ]. More importantly, proteomic explorations of the physiological and pathological dECM of the cardiovascular system will help extract more functional factors such as the VEGF [ 102 ] and MMP2 [ 103 ], which offer critical support for the generation of a more standardized and opulent preparation of 3D-CTE bioink [ 104 , 105 ].…”
Section: Frontier Of 3d Bioprinting In Cardiac Tissue Engineeringmentioning
confidence: 99%